A process integrated engineering knowledge acquisition and management model for a project based manufacturing - Han, Jinteck; Lee, Soo-Hong; Kim, Jae Kwan (KOREAN SOC PRECISION ENG, 2017)
This paper suggests a model for collecting, managing and utilizing engineering outputs integrated with product life-cycle process of project-based industry. Project output acquisition is designed to collect outputs without additional efforts at the time outputs are registered accordingly with the project schedule. Once revision is occurred in the project period, the revision is designed to be transferred to the corresponding process by using ECO (Engineering Change Order) process. To increase usability of the outputs as enterprise knowledge, accumulated outputs are managed and stored by applying multiple classifications from perspectives of process activity, contents, and enterprise knowledge management during accumulation process is carrying out. As a result of applying the suggest system in electric transformer EPC project performing concurrent-multiple project, usability and a degree of accumulating outputs that includes revision history and process accuracy are improved compared to previously used PDM (Product Data Management) system. Although this research is focused on collecting and acquiring project outputs, business process knowledge is supposed to be considered as a significant knowledge content of industries. There has been a research to attach procedure of collecting and acquiring process knowledge into a framework for future.
Keywords: CRITICAL SUCCESS FACTORS; FRAMEWORK; SYSTEMS